2015
DOI: 10.4025/reveducfis.v26i3.26740
|View full text |Cite
|
Sign up to set email alerts
|

Dislipidemia em adolescentes residentes em um município do Paraná e sua associação com a obesidade abdominal

Abstract: RESUMOO objetivo do presente estudo foi verificar as associações da obesidade abdominal, e alterações no perfil lipídico (PL) de adolescentes. Foram selecionados aleatoriamente 650 adolescentesde um município do sudoeste do Paraná. Para a obesidade abdominal mediu-se a circunferência de cintura (CC), para verificar o PL realizou-se coleta sanguínea que determinaram as dosagens de triglicerídeos, colesterol total, lipoproteínas de alta e baixa densidade. Para análise estatística utilizou-se o teste qui-quadrado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
1
0
3

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
(17 reference statements)
1
1
0
3
Order By: Relevance
“…25,26 This study demonstrated an association between HDL-c/TG and WC/BMI, showing the relationship with adiposity. This same association was seen in other studies, such as in the one by Pavão et al, 21 when they evaluated adolescents in a municipality of the state of Paraná and observed a predisposition to dyslipidemia when abdominal obesity, seen through WC, was present. Another study in the city of Recife showed that adolescents with overweight or abdominal obesity had higher values of TG and lower levels of HDL-c. 25 This study had as a limitation a convenience sample, which does not allow the generalization of results.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…25,26 This study demonstrated an association between HDL-c/TG and WC/BMI, showing the relationship with adiposity. This same association was seen in other studies, such as in the one by Pavão et al, 21 when they evaluated adolescents in a municipality of the state of Paraná and observed a predisposition to dyslipidemia when abdominal obesity, seen through WC, was present. Another study in the city of Recife showed that adolescents with overweight or abdominal obesity had higher values of TG and lower levels of HDL-c. 25 This study had as a limitation a convenience sample, which does not allow the generalization of results.…”
Section: Discussionsupporting
confidence: 85%
“…This study presented higher mean values of the lipid profile than others in the literature. 19-21 HDL-c, a lipoprotein that acts as a protective factor against cardiovascular diseases, was the component with the highest change prevalence found among adolescents, as well as in the study by Ribas and da Silva, 2009. 22 Another population-based study with more than 30,000 participants also found similar results.…”
Section: Discussionmentioning
confidence: 59%
“…Martínez-Gómez et al 26 e Pavão et al 27 encontraram associação semelhante entre CC e dislipidemia. É importante destacar que a obesidade central pode ser um importante fator para valores alterados no perfil lipídico e aumento do risco cardiometabólico em adolescentes 26,27 , tornando o VAI um instrumento diagnóstico relevante para avaliação clínica.…”
Section: Discussionunclassified
“…Um estudo realizado por Pavão et al (2015), analisando o perfil lipídico de 650 adolescentes, em uma cidade no sul do país, observou valores semelhantes de HDL aos valores deste estudo (66,7% e 71,4%, para sexo feminino e masculino, respectivamente). Quanto às demais variáveis lipídicas, seus valores foram mais elevados do que os valores expostos neste estudo (30% CT, 20% LDL e 40% TG).…”
Section: Discussõesunclassified